Academic research and researchers - Brew, Angela , 1943-; Lucas, Lisa (Open University Press, 2009)
This book is concerned with how individual researchers experience and respond to this scenario. It brings together research and scholarship examining the socio-political context of university research and explores how researchers' perceptions and identities are changed by political and cultural agendas for research